Factors Influencing Iranian Women\'s Participation in Breast Cancer Screening Programs: A Systematic Review - Alireza Hajizadeh; Salar Mohammaddokht; Sajad Dorri Kafrani; Elham Monaghesh; Jafar Amanzadeh (Journal of Evidence Based Health Policy, Management & Economics, 2023)
Background: Breast cancer screening programs are one of the most important methods for the early detection of breast cancer in women. Several studies have been conducted to identify factors affecting breast cancer screening behaviors among Iranian women. This study is conducted to systematically review the factors influencing women’s participation in breast cancer screening programs in Iran. Methods: Papers were collected by using the keywords breast, mammary, screening, early detection, diagnosis*, examination, testing, and Iran from various English-language databases, including PubMed, Scopus, Web of Science, and databases in Persian language including SID and Magiran. The search was limited to the title and abstract of papers published between January 1, 2000, and May 1, 2021. A narrative synthesis was performed to summarize findings of the obtained papers. Results: In this study, 1345 papers were initially found and, after screening the title, abstract, and full-text, 39 papers were selected. Most of them were cross-sectional (n= 28). Results indicated that socioeconomic factors, individual characteristics, recommendation of health workers, knowledge, Islamic beliefs, support by family, and activities of the Iranian government are frequently mentioned as contributing factors and can be applied to increase participation of Iranian women in breast cancer screening. Conclusion:  The results demonstrate that lack of knowledge and a positive attitude towards breast cancer screening is a major problem regarding Iranian women's non-participation in the screening programs. Therefore, the need for regular implementation of the national screening program in the country, providing appropriate educational methods to increase women's awareness, removing barriers and improving women's access to health care providers should be the priorities of the Iranian health system to prevent breast cancer.